Immunocytochemistry Streptavidin Biotin: Early Detection of Viral Nervous Necrosis Virus in the mucous of the Ikan Kerapu Macan(Epinephelus fuscoguttatus) - Putu Eka Sudaryatma; Artanti Tri Lestari; Ni Luh Sunarsih; Ketut Sri Widiarti; Sulis NurHidayah; Didik Srinoto Srinoto (Jurnal Sain Veteriner, 2012)
Kerapu macan  (Epinephelus fuscoguttatus)    is  one of the  kerapu  fishes  that  has been successfully  bred by the  farmers.  The  survival  rate  of  the  fish  reaches  up  to  the  40%  at  the  fish  hatchery  of  the  home  industry  of  in  Bali. The disease in which may cause significant mortality in kerapu fish, especially for the larvae and juveniles is viral nervous necrosis (VNN). We therefore developed and applied the immunological diagnostic approach of immunocytochemistry technique of streptavidin biotin (SB) for early detection of  VNN. Mucous samples of VNN  infected-  kerapu  fish  in  vivo  were   firstly  detected  by  reverse  transcriptase-polymerase  chain  reaction  (R T -PCR)  for  the  presence  of  DNA  VNN.  If  it  is  RT -PCR-positive  VNN,  the  mucous  samples  were  then  tested  by  SB. Results of the present study indicated that the VNN virus could be detected with SB technique within only 24 hours post infection.  It  was concluded that  rapid  and accurate SB technique  is  suitable and appropriate to  be applied  for  routine  control  and  prevention  national  program  in  the  Fish  Quarantine  for  Indonesia  because  no  need of  fish  sacrification,  and  scientific,  law  and  international    accepted,  and  even  no  hazardous  environmental contamination.Keywords:  kerapu  macan  (Epinephelus  fuscoguttatus),VNN,  mucous,  SB,  early  detection